In vitro Antimycobacterial, Apoptosis-Inducing Potential, and Immunomodulatory Activity of Some Rubiaceae Species - Aro, Abimbola O.; Dzoyem, Jean Paul; Goddard, Amelia; Fonteh, Pascaline; Kayoka-Kabongo, Prudence N.; McGaw, Lyndy J. (Frontiers in Pharmacology, 2019)
Tuberculosis (TB), a disease caused by microorganisms of the Mycobacterium tuberculosis complex, infects almost one-third of the world’s population. The TB epidemic has been further exacerbated by the emergence of multi-and extensively-drug-resistant (MDR- and XDR-TB) strains. The recent evolution of a ‘totally drug-resistant’ TB strain is of great concern due to the limited chance of successful therapy. An effective immune response plays a crucial role in determining the establishment of TB infection. However, this facultative pathogen has devised various mechanisms such as immune-evasion strategies to subvert the host immune response. In this study, the antimycobacterial, immunomodulatory and apoptosis-inducing effects of six Rubiaceae species was evaluated. The results obtained revealed that all the six extracts tested had antimycobacterial activity against M. tuberculosis H37Rv, M. tuberculosis ATCC 25177 and M. bovis ATCC 27299 strains, with MIC values ranging from 39 to 312 µg/mL. Treatment with the acetone extract of Cephalanthus natalensis and Pavetta lanceolata on LPS-stimulated U937 macrophages induced a mixed Th1/Th2 response while the extracts of Cremaspora triflora and Psychotria zombamontana induced a profound Th1 response. The addition of the crude extracts of C. triflora, P. capensis and P. zombamontana at the tested concentrations to the cell culture medium induced apoptosis in a time and dose dependent manner. The microbicidal activity of anti-TB drugs alone is not sufficient, but should include modulation of the host immune response pathways in order to combat the causative pathogen of the disease, thereby synergistically enhancing the activity of the drugs.